2003
DOI: 10.1111/j.1475-2743.2003.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different precipitated phosphates as phosphorus sources for plants

Abstract: Eleven precipitated phosphates were evaluated as sources of phosphorus (P)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(118 citation statements)
references
References 7 publications
11
104
0
3
Order By: Relevance
“…Struvite is an effective phosphorus fertilizer (Johnston and Richards, 2003), which can be stored and transported easily. Basically, struvite is an orthophosphate, containing magnesium, ammonium, and phosphate in equal molar concentrations.…”
Section: Struvite Precipitationmentioning
confidence: 99%
“…Struvite is an effective phosphorus fertilizer (Johnston and Richards, 2003), which can be stored and transported easily. Basically, struvite is an orthophosphate, containing magnesium, ammonium, and phosphate in equal molar concentrations.…”
Section: Struvite Precipitationmentioning
confidence: 99%
“…The assessment of fertilizers based on analytical results alone is not sufficient, because the predicted and actual availability and uptake of P by plants can differ substantially. Johnston and Richards [22] as well as Römer [23] confirmed that some P fertilizers ensure relatively good P availability and supply despite the small amounts contained in water-soluble form. Cabeza et al [17] concluded that the dissolution of P in soil is a much more accurate indicator of the fertilizing effectiveness of recycled P products than their solubility in water or citric acid.…”
Section: Introductionmentioning
confidence: 85%
“…Several previous research studies have exhibited a similar conclusion. 8,20 Compared to other fertilizers, the benefits of using struvite are low leaching rates and prolonged release of nutrients throughout the growing season of plants, 36 which resulted in low leaching losses of nutrients in soil with irrigation and rain. It was also found that higher soil Olsen P could be seen with struvite treatment in both soils.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…It is known that water-soluble P fertilizer is generally considered to be fully plant available, and the P uptake from struvite has been studied in the greenhouse with a variety of test plants on soils compared with commercial P fertilizer. [8][9][10][11] evaluated the availability of urine-derived struvite as fertilizer and found that struvite led to biomass yield and P uptake comparable to or higher than those induced by a commercial mineral fertilizer. A few reports of the comparison of soils with different pH values can be found in previous research.…”
Section: ■ Introductionmentioning
confidence: 99%